Stakeholder perspectives on Relationships and Sex Education outcomes for students with intellectual disability to inform the development of a Core Outcome Set: a qualitative study - Paulauskaite, Laura; Totsika, Vasiliki; Rivas, Carol (Frontiers in Education, 2026)
Little is known about how to deliver Relationships and Sex Education to students with intellectual disability and what outcomes to measure. UNESCO defines Relationships and Sex Education as a part of the curriculum that aims to provide students with comprehensive knowledge, skills and attitudes about their sexuality. Evaluations of Relationships and Sex Education for people with intellectual disability indicate inconsistent outcome measurement and a lack of stakeholder involvement in outcome selection. Development of a Core Outcome Set could address this limitation as it involves identifying a stakeholder consensus-based minimum set of outcomes to be used in research evaluations. This qualitative study explored student and adult stakeholders’ views on important Relationships and Sex Education outcomes for students with intellectual disability to inform a development of a Core Outcome Set. A total of 53 adult stakeholders (students’ parents, teachers, researchers and policy makers) took part in online interviews and workshops. Nineteen students with intellectual disability took part in visual data collection sessions. A list of 31 outcome domains was identified as important by stakeholders. These were grouped into eight themes: the human body and development through the life course; emotions and feelings; healthy relationships and associated social skills; sex and sexuality; keeping safe; consent and communication skills; self-esteem; and the human rights. Stakeholders’ rationale for outcome importance involved unique needs and difficulties experienced by this population. The list of outcomes will be used to establish consensus across stakeholders on the most important outcomes to be included in the Core Outcome Set. The findings provide stakeholder identified strategies for enabling students to achieve the outcomes. This study highlights the importance of including key stakeholders in the initial stages of a Core Outcome Set development and provides methodological insights on how to engage a diverse group of stakeholders.